PENGARUH CUSTOMER KNOWLEDGE MANAGEMENT, KEPUASAN PELANGGAN DAN PERCEIVED VALUE TERHADAP LOYALITAS PELANGGAN YANG DIMEDIASI OLEH KEPERCAYAAN PELANGGAN - Khotimah, Mia Husnul; Sitepu, Adma Sari (JURNAL LENTERA BISNIS, 2025)
This study aims to analyze the influence of customer knowledge management, perceived value, and customer satisfaction on customer loyalty, with customer trust as a mediating variable. Using a quantitative approach with Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software, data was collected from an online survey. The results indicate that customer trust has a positive effect on customer loyalty, reinforcing the importance of building trust in customer relationships. Customer knowledge management significantly influences customer trust and customer loyalty. Customer satisfaction was also found to have a positive influence on customer trust and loyalty, both directly and through the mediation of trust. Additionally, perceived value positively influences customer trust and customer loyalty through trust. These findings suggest that companies should focus on customer knowledge management, enhancing customer satisfaction, and creating perceived value to strengthen customer loyalty.